Experimental Investigation on Failure Modes and Progressive Failure Process of Earthen Check Dam Triggered by Upstream Flow - Zhu, Yanbo; Li, Futong; Yang, Fanfan; Zhang, Yuxuan; Tian, Wanghui; Lan, Hengxing (Frontiers in Earth Science, 2022)
The progressive failure of earthen check dams triggered by upstream flow is common in loess gullies on the Loess Plateau of China. However, studies on the formation mechanism of progressive failure are still unclear. To investigate the failure modes and progressive failure process of earthen check dams, a physical model test on an earthen dam influenced by upstream flow is conducted by monitoring and analyzing hydrological and mechanical parameters, including water content, pore water pressure, soil stress, and displacement. The test results indicate that the progressive failure process of earthen dams is induced by seepage water discharging on the downstream slope, including slope slide and overtopping. The continuous seepage results in the occurrence of the creep at the toe, gradually driving the deformation and sliding of dam slope. The progressive failure begins in the downstream slopes, and this study focuses on analyzing the initiation mechanism of slope slide. The slope failure presents retrogressive sliding, including four repeated slip failures, and each sliding presents a long-time progressive process. This physical model test reproduces the entire life cycle of earthen check dams and reveals the traction sliding mechanism of dams, which is consistent with the field observation. The above results provide an important reference for understanding the failure mechanism of earthen check dams triggered by upstream flow.